Knowledge, Attitudes and Practices Towards Government Order Related to COVID-19 in Public Bus: A Cross-Sectional Study in Bangladesh - Mia, Md Tuhin; Eva, Esrat Jahan; Ahasan, Naima; Mahmud , Hossain; Sikder, Chayon (South Asian Journal of Social Sciences and Humanities, 2025)
Bangladesh currently faces an unavoidable challenge to cope with the COVID-19 pandemic.  In response to surging COVID-19 cases, the government has formulated some legal  frameworks to be implemented in public bus usage during COVID-19. The study aims to  explore the level of Knowledge, Attitudes, and Practices (KAP) among the general people in  response to such framework in the public bus of Dhaka city in Bangladesh. This cross sectional study was conducted with 400 participants (public bus passengers, drivers, helpers  and owners) using the purposive sampling and semi-structured questionnaire survey over  eight months from November 2021 to June 2022. This study illustrates that 100% of  respondents are very well-known about the Coronavirus and 81% reported use of public  buses during COVID-19 is unsafe where cent percent have been taken more or fewer  precautionary steps in using a public bus. Around 30% use masks as a protective measure, of  which 30.2% consider it as government order. About 100% of respondents are very well  known about government order (directives) but 69.2% not obliged to practice these orders in  using public bus where they claimed incognizance of people as a main causal factor of this  less practice. About 54.3% of respondents strongly agreed to use masks and maintain  distance in public buses where 55% hand sanitization, 60.3% cover face during coughing, and  50% avoid closely seating in public buses. It is observed that there is a significant association  between marital status, respondent’s category, knowledge on COVID-19 order and KAP  towards government order (directives) of the public bus at 1% level of significance as where  p
Keywords: Knowledge; Attitude; Practice; Government order; COVID-19; Public bus; Violation